Is Mandarin Chinese a Truth-Based Language? Rejecting Responses to Negative Assertions and Questions - Li, Feifei; González-Fuente, Santiago; Prieto, Pilar; Espinal, M.Teresa (Frontiers in Psychology, 2016)
This paper addresses the central question of whether Mandarin Chinese (MC) is a canonical truth-based language, a language that is expected to express the speaker’s disagreement to a negative proposition by means of a negative particle followed by a positive sentence. Eight native speakers of MC participated in an oral Discourse Completion Task which elicited rejecting responses to negative propositions and broad focus statements (control condition). Results show that MC speakers convey REJECT by relying on a combination of lexico-syntactic strategies (e.g., negative particles such as bù, méi(yǒu), and positive sentences) together with prosodic (e.g., mean pitch) and gestural strategies (mainly, the use of head nods). Importantly, the use of a negative particle, which was the expected outcome in truth-based languages, only appeared in 52% of the rejecting answers. This system puts into question the macroparametric division between truth-based and polarity-based languages and calls for a more general view of the instantiation of a REJECT speech act that integrates lexical and syntactic strategies with prosodic and gestural strategies.